2016
DOI: 10.1159/000441462
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in End-Stage Renal Disease Patients: How Often Should We Ask and What Do We Do with the Answer?

Abstract: Background: End-stage renal disease (ESRD) patients have poor health-related quality of life (HRQOL) comparing to general population and comparable HRQOL to patients with other major chronic diseases. Poor HRQOL is associated with shorter survival. There is a limited threshold to which dialysis dose and parameters management can improve HRQOL in ESRD patients. Numerous studies have sought to find interventions to improve HRQOL. This article is to review the symptoms associated with poor HRQOL and how frequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…Both instruments have been validated, and the KDQOL has emerged as the most widely used tool for healthrelated quality of life assessment in the nephrology literature. In fact, the KDQOL is administered annually to patients on dialysis in the United States to meet the requirements of the Center for Medicare and Medicaid Services for incorporating assessment of health-related quality of life into ESKD care (28).…”
Section: Discussionmentioning
confidence: 99%
“…Both instruments have been validated, and the KDQOL has emerged as the most widely used tool for healthrelated quality of life assessment in the nephrology literature. In fact, the KDQOL is administered annually to patients on dialysis in the United States to meet the requirements of the Center for Medicare and Medicaid Services for incorporating assessment of health-related quality of life into ESKD care (28).…”
Section: Discussionmentioning
confidence: 99%
“…In recognition of the burden of symptoms accompanying end stage kidney disease, patient experience measures are under development internationally to inform patient care needs and clinical quality measures [30]. We have demonstrated that Western understanding of ESRD symptoms differ from Aboriginal peoples understanding of symptoms, but we have enabled a validation of Aboriginal-reported experience and symptom measures and scoring of measures in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Patients with End-Stage Renal Disease (ESRD) face many challenges, including increased burden of comorbidities, reduced life expectancy and impaired quality of life, compared to general population [1,2]. Renal Replacement Therapy (RRT) are lifesaving treatments which include dialysis and kidney transplantation.…”
Section: Introductionmentioning
confidence: 99%